Penggunaan Metode Outdoor Learning dalam Meningkatkan Kemampuan Berbicara Bahasa Arab Peserta Didik Kelas XI MA DDI Lil-Banat Parepare - Haruna, Nur Muthmainna Maryam (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2024)
This study aims to evaluate the effectiveness of outdoor learning method in improving Arabic speaking ability among Grade XI students of MA DDI Lil-Banat Parepare. By focusing on the changes in speaking ability before and after the application of this method, this study seeks to provide an understanding of how this method can affect learning outcomes. This study used an experimental design with a one group pretest-posttest model. The research sample consisted of 12 learners in class XI. Data were collected through pre-test and post-test, each of which contained 15 questions related to Arabic vocabulary and phrases. Treatment in the form of four sessions of outdoor learning method was applied between the pre-test and post-test. Data were analyzed using a quantitative approach with the help of SPSS 21.0 to measure changes in speaking ability. The findings showed a significant improvement in Arabic speaking ability after the application of the outdoor learning method. The mean score of the learners' pre-test was 62.77, while the mean score of the post-test increased to 93.33. The paired sample test resulted in a sig. 0.000, which indicates that this difference is statistically significant. This study adds to the existing literature by demonstrating the specific application of outdoor learning method in the context of Arabic language learning. The results of this study highlight positive changes in learners' speaking ability that have not been widely discussed before in this context. The findings imply that the outdoor learning method can be an effective strategy in improving Arabic speaking skills. The application of this method can be considered for wider application in language learning contexts, especially in environments that require increased learner interaction and engagement.